VNDN 환경하에서 인포테인먼트 응용 이슈 - 이희진(Heejin Lee); 임헌국(Huhnkuk Lim) (한국정보통신학회논문지, 2021)
Recently, many studies on VNDN technology have been conducted to graft Named Data Networking (NDN) into VANET as a core network technology. VNDN can use the content name to deliver various infotainment application content data through name-based forwarding. When VNDN is used as a communication technology for infotainment applications in connected vehicles, it is possible to realize data-centric networking technology in which data is the subject of communication. It can overcome the limitations of connected vehicle infotainment application service technology based on the host-centric current Internet, such as security attack/hacking, performance degradation in long-distance data transmission, frequent data cut-off. In this paper, we present the main functions provided by VNDN technology, and systematically analyze and organize the issues necessary to realize infotainment application services for connected vehicles in the VNDN environment. Based on this, it can be utilized as basic information necessary to establish infotainment application requirements in VNDN environment. 최근 VANET에 Named Data Networking (NDN)을 코어 네트워크 기술로 접목시키기 위한 VNDN 기술 연구가 많이 이루어지고 있다. VNDN은 컨텐트 이름을 사용하여 다양한 인포테인먼트 응용 컨텐트 데이터를 이름 기반 포워딩을 통해 전달할 수 있다. VNDN을 커넥티드 차량의 인포테인먼트 응용을 위한 통신 기술로 활용할 시 데이터가 통신의 주체가 되는 데이터 중심 네트워킹 기술 실현이 가능하며, 차량 보안 공격 및 해킹, 장거리 데이터 전송 시 성능저하, 잦은 데이터 끊김 현상 등 현재의 호스트 중심 인터넷에 기반한 커넥티드 차량의 인포테인먼트 응용 서비스 기술이 갖는 한계를 극복할 수 있다. 본 논문에서는 VNDN 기술이 제공하는 주요 기능에 대해 살펴보고, VNDN 환경하에서 커넥티드 차량들에게 인포테인먼트 응용 서비스를 실현하기 위해 필요한 이슈들에 대해 체계적으로 분석 정리하여 제시한다. 이를 토대로 VNDN 환경하에서 인포테인먼트 응용 요구사항을 정립하는데 필요한 기초 정보로 활용 되어질 수 있을 것이다.